(untitled) (Perner’s Contacts, 2016)
Human resource controlling represents company’s strategic method which role is planning, checking and managing including information supplement for human resource department. The selection of appropriate human resource controlling tools is the most important part of implementation. Our paper deals with the problem of human resource indicators selection as the most fluently used human resource controlling tool. To solve the problem we choose the methodology from Deloitte – Human resource strategy framework. The important part of this methodology is also HR Scorecard and other HR tools. The result is selection of key human resource indicators in the view of the human resource controlling aims.